Modified field analysis of inhomogeneously loaded helical slow-wave structures for twts - Ghosh S.; Jain P.K.; Basu B.N. (My University, 2025)
This paper fills the gap in the previous simplified theory of the analysis of an inhomogeneously-loaded helical slow-wave structure of a TWT in which the radial propagation constants in the different structure regions are considered to be the same; the work uses a simplified method in which the wave impedance at a dielectric-dielectric interface in the structure inhomogeneity is successively transformed inwards. The proposed modified field theory considering different radial propagation constants in the different structure regions, which passes on to the previous simplified theory as a special case, has also been validated against experimental data available elsewhere in the literature. The importance of the present modified approach is shown for large inhomogeneity, large helix-metal envelope separation, and, predominantly, for large helix pitch angles. © 1996 Taylor & Francis Group, LLC.